Mr. Lemoncello's great library race - Grabenstein, Chris (New York : Random House, 2017)
"Mr. Lemoncello holds a contest for his young friends where they must race to bring interesting facts back to his library"--
Sequel to: Mr. Lemoncello's Library Olympics.
"Includes a hidden bonus puzzle!" -- Back cover!
Accelerated Reader
Keywords: Libraries -- Fiction; Contests -- Juvenile fiction; Libraries -- Juvenile fiction; Books and reading -- Juvenile fiction; Eccentrics and eccentricities -- Juvenile fiction; Books and reading -- Fiction; Eccentrics and eccentricities -- Fiction; JUVENILE FICTION / Action & Adventure; JUVENILE FICTION / Books & Libraries; JUVENILE FICTION / Mysteries & Detective Stories; Books and reading -- Fiction